1989
DOI: 10.1002/ajmg.1320330104
|View full text |Cite
|
Sign up to set email alerts
|

Marked clinical difference between two sibs affected with juvenile metachromatic leukodystrophy

Abstract: In a child with enzymatically and histopathologically proven metachromatic leukodystrophy (MLD), the disease pursued a course typical of juvenile MLD characterized by neurological degeneration beginning at age 9 years and ending in death at age 18. A younger brother of the patient was found to have profound deficiency of arylsulfatase A in leukocytes and to excrete five- to 20-fold greater-than-normal amounts of sulfatide in the urine. He was completely free of symptoms attributable to MLD until age 16 when he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 13 publications
1
19
0
Order By: Relevance
“…In 1989, Clarke et al reported two siblings with MLD where one had a much later onset of symptoms as well as a much slower disease progression. 24 In our material, the age of onset was earlier for all three untreated controls, but the disease progression was then equivalent between the sibling pairs. Also, we judge it is more likely that the difference between case controls described in this paper is due to the intervention, rather than because all three pairs happened to have a similar rare intrafamilial variability.…”
Section: Discussionmentioning
confidence: 58%
“…In 1989, Clarke et al reported two siblings with MLD where one had a much later onset of symptoms as well as a much slower disease progression. 24 In our material, the age of onset was earlier for all three untreated controls, but the disease progression was then equivalent between the sibling pairs. Also, we judge it is more likely that the difference between case controls described in this paper is due to the intervention, rather than because all three pairs happened to have a similar rare intrafamilial variability.…”
Section: Discussionmentioning
confidence: 58%
“…22 However, substantial variation of phenotype among patients with the same genotype is well known, and may occur even in affected individuals of the same family. 23,24 Therefore, comparing the index patient not only with affected family members, but also with a cohort of untransplanted MLD patients with standardized and validated tools is necessary to substantiate individual findings and evaluate treatment effectiveness. This case exemplifies a follow-up strategy, which helps to identify patients, who will benefit from HSCT more reliably.…”
Section: Discussionmentioning
confidence: 99%
“…There are, in fact, only a few reported cases of adult MLD without some evidence for psychiatric manifestations. Behavioral problems and decline in school performance are also common initial signs of juvenile onset MLD (Gordon, 1978;MacFaul et al, 1982;Clarke et al, 1989).…”
Section: Preemergent Psychiatric Symptoms Of Late Onset Mldmentioning
confidence: 99%